eNodeB Position Forecasting of LTE Based On BTS Existing Using Fuzzy C-Means and Harmony Search Methods - I Kadek Susila Satwika; Made Hanindia Prami Swari (IJCONSIST JOURNALS, 2019)
Abstract— Fourth generation technology that is 4G LTE (Long Term Evolution) on mobile network has been developed in Indonesia. These developments force telecommunication service providers to upgrade existing infrastructure to the latest technology. The service upgrade process to the latest generation in this 4G LTE service utilizes existing base stations as BTS with the latest technology called eNodeB. In fact, not all existing BTS will be upgraded to eNodeB in the time span until 2020 with consideration of the traffic conditions of 4G LTE users and the resulting coverage. Therefore, a plan is required with a method that can provide solutions in optimizing the utilization of existing base stations as new eNodeB 4G LTE in the city of Denpasar. This research has proposed Fuzzy C-Means method to get eNodeB cluster center point for clustering process followed by optimization process using Harmony Search method. This study uses several variables for the optimization process, including: Denpasar city traffic, number of eNodeB needs in 2020, and coverage of each existing BTS. The result of the planning simulation shows that the optimal existing base station is used as the 123 BTS eNodeB site of 211 BTS, and there are 41 new potential eNodeB points considered optimal with total path loss value of 136085,8338 dB.